15本の過剰埋伏歯を認めた1例 - 五十嵐, 秀光; 山崎, 雅人; 高野, 裕史; 中田, 憲; 福田, 雅幸; 今野, 泰典 (日本口腔外科学会雑誌, 2016)
The prevalence of supernumerary teeth is not rare, estimated to be about 1%. Most supernumerary teeth are located in the maxillary incisor region, and patients with supernumerary teeth appearing in other regions are rare. Furthermore, individuals who have three or more supernumerary teeth without cleidocranial dysostosis are extremely rare.　Here we report the case of a 13-year-old girl with 15 supernumerary impacted teeth, which were found on a panoramic X-ray image and computed tomography (CT).　The panoramic x-ray image showed 15 supernumerary impacted teeth in both sides of the canine and premolar regions of the upper and lower jaws. CT indicated that the roots of all 15 supernumerary teeth were not fully developed, and the teeth were deeply embedded in both sides of the canine and premolar regions of the upper and lower jaws. Because she initially did not have any symptoms, we chose to take a“ wait and see” approach. However, the supernumerary impacted teeth started to show signs of growth and eruption 19 months later and were therefore extracted with the patient under general anesthesia. The extracted supernumerary impacted teeth were histopathologically normal tissues, and the final diagnosis of all 15 teeth was supernumerary impacted teeth.